PENINGKATAN KOMPETENSI GURU MELALUI PENGEMBANGAN MEDIA PENDUKUNG PEMBELAJARAN DEEP LEARNING DI GUGUS PENGAWASAN SEKOLAH KECAMATAN KUTOREJO - Rusminati, Susi Hermin; Susi Hermin Rusminati; Arif Mahya Fanny; Erlin Ladyawati; Apri Irianto (Kanigara, 2026)
This community service activity aimed to improve teachers’ competence through the development of supporting media for deep learning instruction in the School Supervision Cluster of Kutorejo District. The main problems faced by the partners were teachers’ limited understanding of deep learning concepts and their low ability to utilize technology-based learning media. The methods applied included needs analysis, learning media design, training, mentoring, and evaluation. The activity involved 35 teachers and was conducted through workshops and practice-based mentoring. The results showed a significant improvement in teachers’ competencies across all measured aspects, including understanding of deep learning concepts, ability to use digital learning media, confidence in integrating technology, and readiness to apply the media in classroom learning. After the activity, 85.7% of teachers were categorized as having high and very high competence levels. These findings indicate that the development of supporting learning media accompanied by training and mentoring is effective in enhancing teachers’ competence. This program can serve as a model for similar community service activities in other school clusters or regions.